Design and Manufacturing of a Low Cost 3 Axis CNC Router Machine (University of Khartoum Engineering Journal, 2022)
Computer numerical controlled machines (CNC) are playing a huge role in the Industry today. It is capable of producing complex parts in large volumes along with keeping high level of accuracy. This paper presents a simple design of a 3 axis CNC routing Machine. The machine is driven by stepper motors utilizing lead screws and guides manufactured in a local workshop using conventional manufacturing techniques. The machine is controlled by Mach-3 open source software connected to the machine via parallel port and a breakout board which is connected directly to stepper motors. The hand calculation for the design of the lead screws and the sizing of the motor were carried out. The 3D model was built using Computer aided design software. After the fabrication experimental tests were conducted to measure the performance and the accuracy of the CNC.